A meta-analysis of randomized controlled trials examining the effectiveness of carbetocin in reducing intraoperative blood loss during abdominal myomectomy - Abu-Zaid, Ahmed; Baradwan, Saeed; Hafedh, Bandr; Alshahrani, Majed Saeed; Al Baalharith, Maha; Badghish, Ehab; Algreisi, Fahad; Jamjoom, Mohammed Ziad; Alqarni, Saad M. S.; Albelwi, Hedaya; Nazer, Ahmed; Baradwan, Afnan; et al. (Frontiers in Medicine, 2025)
AimThis study aimed to systematically review and meta-analyze randomized controlled trials (RCTs) assessing the clinical efficacy and safety of carbetocin compared to passive control (placebo or no treatment) in the context of abdominal myomectomy.MethodsSix sources of information underwent screening until 13 April 2024. The risk of bias was assessed using the Cochrane Collaboration tool. The results were presented as mean difference (MD) or risk ratio (RR) along with a 95% confidence interval (CI) using a random-effects model.ResultsFive RCTs with 6 arms and 484 patients (carbetocin = 262 and control = 222) were analyzed. The overall risk of bias was “low” in two studies and “some concerns” in three studies. The carbetocin group exhibited significantly lower mean intraoperative blood loss (n = 6 arms, MD = –292.27 mL, 95% CI [−372.5, −212.03], p < 0.001, with very low certainty of evidence), mean change in hemoglobin (n = 6 arms, MD = –0.63 g/dL, 95% CI [−0.94, −0.33], p < 0.001, with low certainty of evidence), rate of blood transfusion (RR = 0.3, 95% CI [0.21, 0.44], p < 0.001, with very low certainty of evidence), and mean operation time (n = 5 arms, MD = −22.98 min, 95% CI [−38.93, −7.02], p < 0.001, with low certainty of evidence). There was no significant difference between both groups regarding the mean hospital stay (n = 2 arms, MD = –0.1 days, 95% CI [−0.27, 0.06], p = 0.21). The sensitivity analyses demonstrated robustness across all outcomes. No major toxicities were reported.ConclusionCarbetocin use was tolerable and associated with considerable declines in intraoperative blood loss and related complications compared with passive control intervention during abdominal myomectomy.